1988
DOI: 10.1080/09553008814551811
|View full text |Cite
|
Sign up to set email alerts
|

Repair Kinetics in Mouse Lung after Multiple X-ray Fractions Per Day

Abstract: The potential advantage for sparing normal tissue damage by hyperfractionation of low-LET radiation may be limited by the repair kinetics of tissues in the irradiated field. Tissues with slow repair kinetics will limit the number of fractions that may be given on the same day. Results are presented for mouse lung treated with a range of doses per fraction using either two or three fractions per day in multiple X-ray fractionation schedules. The results are analysed to determine whether the repair kinetics foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In studies where both acute pneumonitis and late fibrosis endpoints were studied, the a=b ratios tended to be slightly lower for fibrosis. Estimates of repair half-time in lung, based on incidence of pneumonitis, are generally in the range of 0.7-1.2 h (Travis et al, 1987;Parkins et al, 1988;Vegesna et al, 1989;Van Rongen et al, 1990a,b). …”
Section: Experimental Data and Mechanisms Of Damagementioning
confidence: 99%
See 1 more Smart Citation
“…In studies where both acute pneumonitis and late fibrosis endpoints were studied, the a=b ratios tended to be slightly lower for fibrosis. Estimates of repair half-time in lung, based on incidence of pneumonitis, are generally in the range of 0.7-1.2 h (Travis et al, 1987;Parkins et al, 1988;Vegesna et al, 1989;Van Rongen et al, 1990a,b). …”
Section: Experimental Data and Mechanisms Of Damagementioning
confidence: 99%
“…In studies where both acute pneumonitis and late fibrosis endpoints were studied, the a=b ratios tended to be slightly lower for fibrosis. Estimates of repair half-time in lung, based on incidence of pneumonitis, are generally in the range of 0.7-1.2 h Parkins et al, 1988;Vegesna et al, 1989;Van Rongen et al, 1990a,b). Some studies have identified two components of repair: a fast component with a half-life of 0.4 h (dominating the effect), and a slow component with a half-life of 4 h (Van Rongen et al, 1993).…”
Section: Experimental Data and Mechanisms Of Damagementioning
confidence: 99%
“…Though there have been several experiments providing repair rates for normal lung tissue, many of which indicate the presence of both a short and long component of repair, similar analyses for lung tumors do not exist. [16][17][18][19][20][21] One study of normal lung tissue in mice showed that the slower component of repair may approach T 1=2 ¼ 4.0 h. 22 As previously stated, although no evidence indicating similar results in lung tumors exists, if T 1=2 does approach 4.0 h for lung tumors, the effectiveness of this present study would greatly diminish. Nevertheless, Fowler and Chappell did indicate a rapid repopulation of NSCLC during radiation therapy which may imply a fast component of sublethal damage repair.…”
Section: Iic Benchmarking the Lpl Modelmentioning
confidence: 58%
“…As previously stated, studies have indicated that the use of multiple repair half-times are more accurate when studying repair kinetics. [16][17][18][19][20][21] Fowler et al suggested survival fraction calculations using a weighted average of the G-factor. The value of G(t) is calculated for each value of T 1=2 , properly weighted and then added together to get the effective G(t).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noted that the capacity for toxicity recovery is likely to be decreased more in tumor cells than in normal cells and is expected to be heterogeneous in each type of cancer cell [17][18][19][20]. Moreover, it is not known if the repair capacity of tumor cells recovers in a short period of a few days [21][22][23][24]. Thus, it is challenging to determine whether the interrupted conditioning decreases anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%